2015
DOI: 10.1177/009164711504300406
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Cross-Cultural Healthcare Missionaries

Abstract: In this study of career healthcare missionaries (N = 393), 47.9% of female missionaries and 42.1% of male missionaries reported experiencing anxiety, while 32.5% of female missionaries and 27.5% of male missionaries reported experiencing depression. For both females and males, depression severity scores showed a bimodal distribution of more and less severe depression, suggesting a clearer delineation for mild and severe depression. Regression analyses found that low role satisfaction was associated with both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Positive religious coping embodies the experience of God as director, enabler and supportive partner. Positive religious coping has a notable stressbuffering effect, with more positive caregiver health outcomes [6]. Importantly, positive religious coping was implicit in the universal response of strengthened relationship with God as a result of the caring role, for missionaries in this study.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Positive religious coping embodies the experience of God as director, enabler and supportive partner. Positive religious coping has a notable stressbuffering effect, with more positive caregiver health outcomes [6]. Importantly, positive religious coping was implicit in the universal response of strengthened relationship with God as a result of the caring role, for missionaries in this study.…”
Section: Discussionmentioning
confidence: 69%
“…Strand and workers [6] emphasised the vulnerability of cross cultural missionaries to mental health challenges. They cited the high incidence of depressive and adjustment disorders among this population, and the ensuing decrease in their health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,25 The PRISM Study found 60.1 and 65.8% of men and women to have experienced a moderate to serious bout of anxiety, and 45.0 and 55.5% of men and women to have experienced a moderate to serious bout of depression. 26 As a baseline for comparison, the lifetime prevalence of depression among physicians in the U.S. is 12% for men age 45-54 and 19.5% for women, although the method of measurement used was different from that used in the PRISM Study. 27 Anxiety and depression are distinct but related psychological conditions, 28 with comorbid anxiety present in 50% of persons with major depression.…”
Section: Mental Healthmentioning
confidence: 99%
“…Trimble (2006) leveraged insights and constructs from organizational psychology (i.e., organization commitment and job satisfaction) to help mission organizations reduce preventable attrition. Similarly, Strand, Pinkston, Chen, and Richardson (2015) spoke of the importance of role satisfaction in the mental health of missionary healthcare workers.…”
mentioning
confidence: 99%